2011
DOI: 10.1371/journal.pntd.0001239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Schistosomiasis and Soil-Transmitted Helminth Infections on Physical Fitness of School Children in Côte d'Ivoire

Abstract: BackgroundSchistosomiasis and soil-transmitted helminthiasis are important public health problems in sub-Saharan Africa causing malnutrition, anemia, and retardation of physical and cognitive development. However, the effect of these diseases on physical fitness remains to be determined.MethodologyWe investigated the relationship between schistosomiasis, soil-transmitted helminthiasis and physical performance of children, controlling for potential confounding of Plasmodium spp. infections and environmental par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 40 publications
7
45
2
Order By: Relevance
“…Our findings are in agreement with a recent study assessing physical fitness in Kenyan schoolchildren, which identified nutritional deficiencies as major predictors for impaired physical fitness performance, whilst there was no robust association with parasitic diseases [13]. These observations might also explain why the VO 2 max estimates from the current and a previous study in Côte d’Ivoire [14] were comparable with findings from the Kenyan study, where the extent of malnutrition and anaemia was similar. In contrast, a cohort of school-aged children in Yunnan province, People’s Republic of China, had a strikingly high rate of stunting and helminth infections [15, 21], and VO 2 max estimates and strength test scores were substantially lower than in age-matched African children [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in agreement with a recent study assessing physical fitness in Kenyan schoolchildren, which identified nutritional deficiencies as major predictors for impaired physical fitness performance, whilst there was no robust association with parasitic diseases [13]. These observations might also explain why the VO 2 max estimates from the current and a previous study in Côte d’Ivoire [14] were comparable with findings from the Kenyan study, where the extent of malnutrition and anaemia was similar. In contrast, a cohort of school-aged children in Yunnan province, People’s Republic of China, had a strikingly high rate of stunting and helminth infections [15, 21], and VO 2 max estimates and strength test scores were substantially lower than in age-matched African children [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“…Like two recently published studies evaluating the 20-m shuttle run as a tool for measuring exercise tolerance in polyparasitized children and other studies that tested running performance in children, [53][54][55] we did not find an association with S. mansoni infection. The 20-m shuttle run was originally developed and validated in children from developed countries as a tool to measure maximal exercise capacity by correlation to VO 2 max.…”
Section: Discussionsupporting
confidence: 65%
“…if the subject starts level 4 and only completes two of the shuttles, the recorder will note “4” as the highest level reached and “2” as the number of shuttles completed at the highest level. These numbers are correlated to a maximal oxygen uptake, the VO 2 max in mL/kg/min [12]. …”
Section: Methodsmentioning
confidence: 99%